Case of Solid Pseudopapillary Neoplasm of Pancreas - M. Hamzaçelebioğlu; O. Üreyen; A. Argon; E. İlhan; A. Mert Ateşci (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: to discuss the clinical presentation, management, and outcome of the clinical case of solid pseudopapillary tumour of the pancreas (SPTP).Key points. SPTPs are rare tumours known for their low malignant potential. They are predominantly found in younger females, typically occurring in the tail of the pancreas. Surgical resection of SPTP with negative margins is associated with improved survival rates and lower chances of recurrence. In this study, we discuss the case of a 69-year-old woman diagnosed with an SPTP originating from the tail of the pancreas, which had spread to the hilum of the spleen. A radical resection was performed, successfully obtaining negative surgical margins. However, the patient subsequently developed metastasis to the liver and lungs, prompting the initiation of systemic chemotherapy. The patient died seven months after the development of metastasis and 39 months following the primary diagnosis. This case underscores that, despite initial successful surgical outcomes, high-risk histopathological features can lead to recurrence and metastasis, necessitating reassessment of treatment strategies.Conclusion. Negative surgical margins are critical for a favourable prognosis in the treatment of SPTPs; however, close monitoring for potential recurrence is essential. Our findings highlight that even after achieving negative margins, patients with high-risk features should undergo rigorous follow-up and consider postoperative systemic chemotherapy. This clinical case emphasizes the complexity of managing SPTP and the need for individualized treatment strategies, as early detection of recurrence can significantly influence survival outcomes.